2022
DOI: 10.1002/wsb.1331
|View full text |Cite
|
Sign up to set email alerts
|

A menu of climate change adaptation actions for terrestrial wildlife management

Abstract: The real-world application of climate change adaptation practices in terrestrial wildlife conservation has been slowed by a lack of practical guidance for wildlife managers. Although there is a rapidly growing body of literature on the topic of climate change adaptation and wildlife management, the literature is weighted towards a narrow range of adaptation actions and administrative or policy recommendations that are typically beyond the decision space and influence of wildlife professionals. We developed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…This study identified the hornbill as highly vulnerable to heatwaves with extremely high exposure and high susceptibility. Species classified as being highly vulnerable should be prioritized for monitoring responses to heatwaves and for risk-mitigation actions (Foden et al, 2013;Handler et al, 2022). In contrast, exposed bird species with relatively lower susceptibility are a lower priority for risk-mitigation actions to heatwaves in the near future (Foden et al, 2013;Zhang et al, 2019) still be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified the hornbill as highly vulnerable to heatwaves with extremely high exposure and high susceptibility. Species classified as being highly vulnerable should be prioritized for monitoring responses to heatwaves and for risk-mitigation actions (Foden et al, 2013;Handler et al, 2022). In contrast, exposed bird species with relatively lower susceptibility are a lower priority for risk-mitigation actions to heatwaves in the near future (Foden et al, 2013;Zhang et al, 2019) still be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized and proactive approaches to manage wildlife disease are still relatively uncommon, despite widespread agreement that taking prevention and early action is likely more effective than triaging a large outbreak Table 1. Example adaptation strategies (from Handler et al 2022) that relate to the epidemiological triad (environment, host, and agent) and associated questions to ask during the initial planning phase of a climate adaptation project that link to the checklist of disease risk factors (presented in Figure 3).…”
Section: Anticipate Emerging Disease Threatsmentioning
confidence: 99%
“…Habitat restoration and creation are commonly proposed adaptive management strategies to buffer the impacts of climate change on wildlife communities and populations [1]. These strategies maximize the resilience of communities and/or populations to environmental change through promoting habitat conditions that provide refugia for extant and future wildlife species [2,3]. Habitat restoration and creation are expensive activities that often require intensive management practices [4].…”
Section: Introductionmentioning
confidence: 99%